NON-PERFORMING FINANCING RISK ANALYSIS: AN ISLAMIC RURAL BANK DURING PANDEMIC COVID-19 - Laurin Azwita; Wahyudi, Rofiul (Universitas Muhammadiyah Surabaya, 2023)
One of the problems faced by BPR Syariah in distributing financing is the risk of default. This study aims to analyze the risk of non-performing financing during the Covid-19 pandemic at BPR Syariah BDW. This study uses a qualitative method with a case study approach. The research subjects focused on the head of the marketing department, account officer, and director of BPR Syariah BDW. This research was conducted for two months, from March to April 2021. Data collection used observation techniques, in-depth interviews, and documentation. The research findings show that BPR Syariah BDW during the COVID-19 pandemic has implemented appropriate steps in identifying, measuring, monitoring, and controlling some of the risks faced. Furthermore, BPR Syariah carries out effective internal control, starting from identification to evaluating types of risk.